Dinamika Lingkungan Kerja dan Kompensasi: Kunci untuk Membangun Loyalitas Pegawai - Sutoro, Moh. (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Employee loyalty is a key factor in improving organizational performance and stability. The dynamics of the work environment and an effective compensation system can play an important role in building such loyalty. This research was conducted to understand the influence of the work environment and compensation on employee loyalty at the Tigaraksa Religious Court. This research aims to analyze the relationship between the dynamics of the work environment and compensation and employee loyalty at the Tigaraksa Religious Court. This research uses a quantitative approach with linear regression analysis techniques. Data was collected through a survey involving 112 respondents who were employees of the Tigaraksa Religious Court. The sampling technique used was simple random to ensure sample representativeness. The results of the analysis show that both the dynamics of the work environment and compensation have a significant influence on employee loyalty. Specifically, it was found that improvements in the quality of the work environment and satisfaction with compensation significantly increased employee loyalty levels.